2014
DOI: 10.6028/jres.119.019
|View full text |Cite
|
Sign up to set email alerts
|

Porosity Measurements and Analysis for Metal Additive Manufacturing Process Control

Abstract: Additive manufacturing techniques can produce complex, high-value metal parts, with potential applications as critical metal components such as those found in aerospace engines and as customized biomedical implants. Material porosity in these parts is undesirable for aerospace parts - since porosity could lead to premature failure - and desirable for some biomedical implants - since surface-breaking pores allows for better integration with biological tissue. Changes in a part’s porosity during an additive manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(131 citation statements)
references
References 20 publications
4
114
0
1
Order By: Relevance
“…Fatigue and crack propagation properties of additive manufactured materials are not very well known yet [1], because a lack of process understanding and a lack of in situ process monitoring and control, especially in metal AM systems, currently results in unknown porosity levels and distributions [2]. Multiple sources report a reduced fatigue lifetime.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…Fatigue and crack propagation properties of additive manufactured materials are not very well known yet [1], because a lack of process understanding and a lack of in situ process monitoring and control, especially in metal AM systems, currently results in unknown porosity levels and distributions [2]. Multiple sources report a reduced fatigue lifetime.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…This monitoring aimed to provide an in-situ pass/fail status for parts, defined by tolerancing of the resultant part porosity as measured post-process by XCT. Slotwinski et al [73] developed a method of in-situ porosity monitoring by ultrasonic sensing, correlating ultrasonic porosity data to porosity data gained using three other methods; mass/volume, the Archimedes method and XCT. The authors in this instance noted that porosity values varied significantly between measurement procedures and so further destructive testing would be required to ascertain the "true" porosity value.…”
Section: Hybrid Porosity Measurementsmentioning
confidence: 99%
“…Slotwinski et al used finite element analysis (FEA) and micro-CT scanning of Co-Cr samples manufactured by selective laser melting (SLM) to show that the intrinsic porosity itself did not lead to elastic anisotropy. [11] Leicht & Wennberg found only small differences in the elastic modulus of SLM Ti-6Al-4V in the build plane and normal to the build plane, but these disappeared after stress relief of the samples. [12] Simonelli et al found no variation in elastic modulus of SLM Ti-6Al-4V with build orientation due to the weak a 0 texture of the as-built material.…”
Section: Introductionmentioning
confidence: 99%